Genome-wide association mapping of QTL underlying seed oil and protein contents of a diverse panel of soybean accessions. (January 2018) - Li, Ying-hui; Reif, Jochen C.; Hong, Hui-long; Li, Hui-hui; Liu, Zhang-xiong; Ma, Yan-song; Li, Jun; Tian, Yun; Li, Yan-fei; Li, Wen-bin; Qiu, Li-juan
Highlights: Six putative novel QTNs were identified for oil and protein contents respectively. A new association exhibited pleiotropic effects on seed protein and oil contents. A genetic region associated with oil content was subject to strong selection. Abstract: To investigate the genetic basis of variation in oil and protein contents in soybean seeds, a diverse collection of 421 mainly Chinese soybean cultivars was genotyped using 1536 SNPs, mostly from candidate genes related to acyl-lipid metabolism and from regions harboring known QTL. Six significant associations were identified for each of seed oil and protein contents which individually explained 2.7–5.9% of the phenotypic variance. Six associations occurred in or near known QTL and the remaining are putative novel QTL. Ten significant associations influenced the oil content without decreasing protein content, and vice versa. One SNP was pleiotropic, with opposite effects on oil and protein contents. The genetic region covering Map-6076 and-6077 was shown to be involved in controlling oil content in soybean by integrating the results of association mapping with information on known QTL and tissue-specific expression data. This region was subject to strong selection during the genetic improvement of soybean. Our results not only confirm and refine the map positions of known QTL but also contribute to a further elucidation of the genetic architecture of protein and oil contents in soybean seeds by identifying new associations exhibiting pleiotropic effects on seed protein and oil contents.